A fundamental perspective on the effects of sulfur modification for transition metal nanocatalysts - Kolpin, A (2014)
The application of heterogeneous catalysts to industrial processes is a key factor in the synthesis of nearly all chemicals currently produced, however billions of pounds are lost every year due to unplanned reactor shutdowns and catalyst replacement as a result of catalytic deactivation processes. Poisoning of heterogeneous catalysts by sulfur compounds is a particularly prominent class of deactivation processes, affecting a wide range of catalytic materials and catalytic reactions, including the industrially-prominent Haber-Bosch process for the synthesis of ammonia and steam reforming of methane for the synthesis of hydrogen. However, while the effects of sulfur adsorption on catalytic behaviour are often unmistakably apparent, the fundamental interactions leading to these effects are not yet well understood. The work presented in this thesis uses a combination of models systems, novel and traditional characterization techniques, and methods of modifying catalyst geometric and electronic structure to approach the topic of sulfur poisoning from a fundamental perspective. Particular focus is placed on using selective decoration of active sites to develop a system of model hydrogenation reactions to relate changes in catalytic behaviour to changes in geometric and electronic structure. Application of these model reactions to investigate the sensitivities of palladium- and ruthenium-based catalytic systems to modification by sulfur shows contrasting effects for the two metals. While both systems exhibit similar geometric effects of modification, the palladium-based catalysts are far more sensitive than the ruthenium-based catalysts to modification of electronic structure. Additionally, controlled variation in particle size for the palladium-based catalysts demonstrates that catalytic behaviour is dominated by electronic structure for small nanoparticles and geometric structure for large nanoparticles. This leads small nanoparticles to show increased sensitivity to electronic modification effects resulting from sulfur adsorption. Ultimately, the research presented within this thesis provides a basis for the intelligent design of heterogeneous catalysts for improving tolerance for sulfur poisoning, and for utilizing the effects of sulfur modification to optimize catalytic activity and selectivity for the synthesis of fine chemicals.